PERAN PEMERINTAH DAERAH DALAM PEMBINAAN KEAMANAN JAJAN PANGAN ANAK SEKOLAH DASAR - Aini, Siti Qorrotu (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah (BAPPERIDA) Kabupaten Pati, 2018)
ENGLISHIt is important to pay attention regarding the safety of snack for elementary school children because it affects the quality of health of school children. The safety of snacks for elementary school children is a responsibility for stakeholders in particular government institutions. This research aimed to find out how the local government in the guidance of snacks for elementary students in Pati Regency as well as the barriers for implementing it. This research used descriptive exploratory methode with qualitative approach. The data collected through in-depth interview, observation, and document study. The results showed that the policy for food safety from elementary students have not been specifically stated in the strategic plan of related government institutions. The role of the local government to improve the security of snack for elementary students is conducted implicitly in related service programs from the office of health and the office of education and culture. The constraints comes from budget limitation, the absense of local regulation and low awareneess regarding food safety among elementary students, teachers / principals, and food sellers. INDONESIAPangan jajanan anak sekolah dasar sangat penting mendapat perhatian karena berdampak terhadap kualitas kesehatan anak sekolah. Keamanan pangan jajanan anak sekolah dasar menjadi tanggungjawab bersama antara pemangku kepentingan khususnya pemerintah. Penelitian ini bertujuan untuk mengetahui bagaimana peran pemerintah daerah dan kendala dalam pembinaan pangan jajanan anak sekolah di Kabupaten Pati. Penelitian ini menggunakan pendekatan deskriptif eksploratif. Pengumpulan data diperoleh dengan wawancara mendalam, observasi dan telaah dokumen instansi terkait. Analisis data dengan analisis kualitatif. Hasil penelitian menunjukkan bahwa kebijakan keamanan pangan jajanan anak sekolah dasar belum tertuang secara khusus di dalam rencana strategis (renstra). Peran pemerintah dalam upaya peningkatan keamanan pangan jajanan anak sekolah dasar secara implisit dalam program dinas terkait, yaitu Dinas Kesehatan dan Dinas Pendidikan dan Kebudayaan. Kendala dalam pelaksanaan pembinaan keamanan pangan jajan anak sekolah yang sudah berjalan, diantaranya berupa keterbatasan anggaran, belum adanya peraturan daerah yang mengatur masalah tersebut, serta rendahnya kesadaran akan pentingnya keamanan pangan pada siswa, guru/kepala sekolah, dan penjaja makanan.